Walter Benjamin e Paris: individualidade e trabalho intelectual - Ortiz, Renato (Tempo Social, 2000)
This paper is an interpretation of Walter Benjamins Paris, Capital of the 19th Century. Based on the notes Benjamin made on several books he read, mainly during his research at the Bibliotèque Nationale, the author discusses the notion of the individual linking it to two themes. First, to the emergence of the flâneur as a translation of the spirit of mobility which starts with modernity. The discussion on the notion of space, especially where it concerns Paris, is essential for this analysis. The flâneur is seen as an uprooted individual who moves around the remodelled urban space. Second, to the proximity between the act of flânerie and that of intellectual work. Taking flânerie to be intellectual activity, the author shows how the themes of the distancing and the construction of the object are relevant, both to the detective-flâneur and to the reflection in social sciences.